Analysis of student responses to online learning in biology subjects at Senior High School of Central Lombok - Nova Listiana; Dadi Setiadi; Kusmiyati Kusmiyati (Jurnal Pijar Mipa, 2022)
The current Covid-19 pandemic has a significant impact on all aspects of human life, one of which is in the field of education. This study aims to determine how the senior high school students of North Batukliang central Lombok Indonesia respond to online learning in biology subjects. This research is qualitative descriptive research. The sampling technique in this research is saturated sampling. Meanwhile, the instruments used in this study were interviews and questionnaires. The study showed a positive response: the understanding indicator obtained a student response of 61%, and the independence indicator was 67%, which was included in the strong category. In the facility indicator, the student response value is 79% which is in a very strong category. The learning process still needs to be optimized and needs to be evaluated for the sake of improving online learning in the next period.